Theoretical investigations on the Energy gap, UV- Vis Spectrum and Thermochemical Properties of PVA doped with ZnO andTiO2 - Huda M. Jawad (Wasit Journal for Pure Sciences)
Different polymers have attractive multiple properties due to their uses in many fields. The synthesized polymer polyvinly alcohol (PVA) with metal oxide nanoparticles has many applications in different approaches, such as electronics, sensors, optical,  optoelectronics, and biomedical fields.  The study was carried out within the framework of density functional theory  with B3LYP and exchange- correlation energy functionals 6-31G(d, p).  Three compounds  were PVA and PVA synthesized with zinc oxide (ZnO) and Titanium dioxide (TiO2) nanocomposites. The results proved  that using these oxides is a good way to improve the electronic properties of PVA as the energy gap of PVA decreased from 3.8 to 3.4 eV and 3.3 eV PVA/TiO2 and PVA/ZnO, respectively. This demonstrates the good semiconductor character of these compounds with applications related to solar cell manufacturing. The  photosensitivity of both PVA/TiO2 and PVA/ZnO  samples in FTIR and UV-Vis results indicated that TiO2 and ZnO  interacted strongly with PVA. So they can be used in other applications, such as energy storage capacitors. The vibrational mode were then analyzed in terms of force constant and reduced mass, which were relatively constant hydrogen vibrations.